A qualitative study of the knowledge, behaviour and attitudes of patients with skin cancer regarding sunlight exposure and vitamin D. Issue 4 (22nd May 2017) - Rutkowski, David; Farrar, Mark D.; Osman, Joanne E.; Webb, Ann R.; Rhodes, Lesley E.
Summary: Background: Solar UVR is a major cause of skin cancer but also an important source of vitamin D (VitD), essential for musculoskeletal health. Conflicting public health messages may confuse patients with skin cancer prone to further skin cancer. Objective: To explore the knowledge, behaviour and attitudes of patients with skin cancer to sunlight exposure and VitD sources. Methods: Patients ( n = 10) previously treated for multiple basal cell cancer in a hospital setting participated in focus group sessions with semi‐structured discussions to explore: knowledge of VitD, sun‐avoidance behaviour and attitude towards sunlight exposure messages. Thematic data analysis was performed using software programme MAXQDA11. Results: Pre‐existing knowledge of VitD was low. Most patients practised sun avoidance and were not inclined to increase exposure. Patients did not perceive VitD deficiency as a substantial risk to their own health, or a need to take VitD supplements. They aimed to increase VitD status through dietary intake, but knowledge of food VitD content was lacking. Conclusions: The patients with skin cancer, appropriate to their heightened skin cancer risk, appeared unlikely to increase their sun exposure to gain VitD. However, education is required regarding the generally low levels of VitD in foodstuffs, and the requirement for supplements/fortified foods if strict sun avoidance is employed.